Being both a grandmother and a health worker: experiences of community-based health workers in addressing adolescents' sexual and reproductive health needs in rural Zambia - Chama Mulubwa; Joseph Mumba Zulu; Anna-Karin Hurtig; Isabel Goicolea (BMC, 2024)
Abstract Introduction Community-based health workers (CBHWs) possess great potential to be the missing link between the community and the formal health system for improving adolescents' access to sexual and reproductive health and rights (SRHR) information and services. Yet, their role in addressing adolescents' SRHR within the context of the community-based health system has received very little attention. This paper analyses how CBHWs experience and perceive their role in addressing adolescents' SRHR needs in rural Zambia, including the possible barriers, dilemmas, and opportunities that emerge as CBHWs work with adolescents. Methods Between July and September 2019, we conducted 14 in-depth interviews with 14 community-based health workers recruited across 14 different communities in the central province of Zambia. The interviews were focused on eliciting their experiences and perceptions of providing sexual and reproductive health services to adolescents. Charmaz's grounded theory approach was used for the analysis. Results We present the core category "being both a grandmother and a CBHW", which builds upon four categories: being educators about sexual and reproductive health; being service providers and a link to SRHR services; being advocates for adolescents' SRHR; and reporting sexual violence. These categories show that CBHWs adopt a dual role of being part of the community (as a grandmother) and part of the health system (as a professional CBHW), in order to create/maximise opportunities and navigate challenges. Conclusion Community-based health workers could be key actors providing context-specific comprehensive SRHR information and services that could span all the boundaries in the community-based health system. When addressing adolescents SRHR, playing dual roles of being both a grandmother and a professional CBHW were sometimes complimentary and at other times conflicting. Additional research is required to understand how to improve the role of CBHWs in addressing adolescents and young people's sexual and reproductive health.